Unusual presentation of Campylobacter diarrhea in a 12-week-old infant: a case report - Putcha, Sahithi (International Journal of Contemporary Pediatrics, 2023)
Campylobacter infection is a common cause of bacterial gastroenteritis in children. However, it typically presents with symptoms such as fever, diarrhea, and abdominal pain. We reported an unusual case of Campylobacter diarrhea in a 12-week-old infant who initially presented with decreased appetite and blood in stool, without fever or diarrhea. Then subsequently infant had developed fever and diarrhea. The case highlights the importance of considering atypical presentations of Campylobacter infection in young infants, leading to timely diagnosis and appropriate management.